1998
DOI: 10.14430/arctic1044
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Digestibilities of Summer Forages Utilized by the Rivière George Caribou Herd

Abstract: ABSTRACT. The Rivière George caribou herd (northern Québec-Labrador, Canada) is thought to be regulated by forage limitations in its summer range. In such a situation, digestibilities of plants may strongly affect the diet choice and physical condition of animals. In vitro dry matter disappearance (IVDMD) of the most important summer forages of the Rivière George caribou herd was determined during fermentation periods of 12, 24, and 48 h using rumen fluid collected from a Holstein cow. IVDMD values for Cyperac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…). Graminoids are most important to Rangifer nutrition early and late in the summer when their nitrogen concentration and digestibility are high relative to other species (Appendix ; Côté , Johnstone et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). Graminoids are most important to Rangifer nutrition early and late in the summer when their nitrogen concentration and digestibility are high relative to other species (Appendix ; Côté , Johnstone et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…, Skarin et al. ) and digestibility (White and Trudell , Côté ). Preferred forage has relatively high digestibility and high protein content (White and Trudell , Côté ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors other than, or in interaction with, dietary fiber may also be involved in DMD (Robbins et al 1987a, b) and thus in the selection we observed. Fiber may affect DMD in subtle ways, and only through in vitro or in vivo digestibility trials conducted with deer inoculum could these effects be teased out (Pearson et al 1980, Côté 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Rumen fill is determined by the quantity of vegetation ingested and foraging bout frequency, which in turn are limited by retention time, because short transit times allow more vegetation to be ingested (Renecker and Hudson 1986;Domingue et al 1991). Retention time is influenced by vegetation quality, since the digestion of cell walls increases with retention time (Côté 1998). Hence, an animal foraging on poor quality vegetation-for example, during winter-will tend to increase retention time (Gross et al 1996).…”
Section: Introductionmentioning
confidence: 99%